FRI0277 Six-Minute Walk Test in Systemic Sclerosis Patients without Interstitial Lung Disease and Pulmonary Arterial Hypertension. (15th July 2016) - Vandecasteele, E.; Melsens, K.; De Keyser, F.; De Pauw, M.; Deschepper, E.; Decuman, S.; Piette, Y.; Brusselle, G.; Smith, V.
Abstract : Background: Interstitial lung disease (ILD) and pulmonary arterial hypertension (PAH) are the leading causes of death in Systemic Sclerosis (SSc). Although the six-minute walk test (6MWT) is used for evaluating ILD and PAH in clinical practice, no data are available on six-minute walk distance (6MWD) in SSc without ILD and PAH. Objectives: This study wants to evaluate the 6MWT at baseline and 6-month follow-up in a cohort of unselected SSc patients without ILD and PAH. Methods: Prospectively collected data of the 6MWTs at baseline and 6-month follow-up of 300 consecutive SSc patients, included in the Ghent University Hospital Systemic Sclerosis Cohort between May 2006 and April 2015 were analysed. Results: 98% (286/292) of the SSc patients performed a 6MWT at baseline or 6-month visit, after exclusion of 8 of the 300 SSc patients due to logistic problems. Two patients were unable to perform a 6MWT due to leg amputation and 4 due to immobility. 76% of the patients were female with a mean age of 51±14 years. Six patients had PAH, five had ILD and four were not evaluated with HRCT. Eventually 271 SSc patients without ILD and PAH performed a 6MWT at baseline or 6-month visit and 193 at both moments. The mean 6MWD of those 271 SSc patients was 460±108m. Patients in the diffuse cutaneous (DcSSc) subgroup (422±118m) walked less than in the limited (LSSc) subgroup (476±109m, p=0.02) and tended to walk less than in the limited cutaneous (LcSSc) subgroup (463±101m, p=0.06). In 193 SSc patients without ILD and PAH who walked at both moments, there was no significant difference between the 6MWDs (mean difference 2.11m 95%CI [-6.75m; 10.98m], p=0.64). Conclusions: In SSc, execution of the 6MWT is feasible, as 98% of the SSc patients were able to perform a test. The baseline mean 6MWD of 271 SSc patients without ILD and PAH is 460±108m and is clinically stable over a 6 months period. The DcSSc subgroup walks less than the LSSc subgroup and the LcSSc subgroup. Disclosure of Interest: None declared